DAMPAK ALOKASI ANGGARAN PENGELUARAN PEMBANGUNAN TERHADAP PEREKONOMIAN INDONESIA: SUATU ANALISIS SIMULASI KEBIJAKAN - BONAR M. SINAGA; ANTON HENDRANATA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2005)
This study aims (1) to construct Econometric Input-Output Model for Indonesia,which emphasizes the linkage between sectors, and (2) to analyze the impact of budgetallocation policy of development expenditure on Indonesian economy.The model, which construct by combining the advantages of input-output modeland econometric model, is called Model Input-Output Ekonometrika Indonesia. Themodel consists of 112 dynamic simultaneous equations, and it uses secondary data from1980-2000. The equation’s parameters are estimated by using the combination of threeestimation methods: (1) Ordinary Least Squares, (2) First Order of Autoregressive, and(3) Second Order of Autoregressive. The model is validated by Gauss-Siedel Methodand it is used for policy simulation analysis of budget development expenditure.The study shows that the impact of budget reallocation of developmentexpenditure on Indonesian economy (final demand, output, income, and sectoralemployment) is better than the budget allocation of development expenditure inRAPBN (National Budgetary Plan) 2002. Plantation sector gave the highestcontribution in supporting the output multiplier and high income. Furthermore, the food,beverages, and tobacco industries gave the highest contribution in creating highemployment multiplier.